Cardiac, renal, and neurological benefits of preoperative levosimendan administration in patients with right ventricular dysfunction and pulmonary hypertension undergoing cardiac surgery: evaluation with two biomarkers neutrophil gelatinase-associated lipocalin and neuronal enolase - Guerrero-Orriach JL; Ariza-Villanueva D; Florez-Vela A; Garrido-Sánchez L; Moreno-Cortés MI; Galán-Ortega M; Ramírez-Fernández A; Alcaide Torres J; Santiago Fernandez C; Navarro Arce I; Melero-Tejedor JM; Rubio-Navarro M; et al. (Dove Medical Press, 2016)
José Luis Guerrero-Orriach,1 Daniel Ariza-Villanueva,1 Ana Florez-Vela,1 Lourdes Garrido-Sánchez,2,3 María Isabel Moreno-Cortés,1 Manuel Galán-Ortega,1 Alicia Ramírez-Fernández,1 Juan Alcaide Torres,3 Concepción Santiago Fernandez,3 Isabel Navarro Arce,1 José María Melero-Tejedor,4 Manuel Rubio-Navarro,1 José Cruz-Mañas1 1Department of Cardio-Anaesthesiology, University Hospital Virgen de la Victoria, Málaga, Spain; 2CIBER Fisiología de la Obesidad y Nutrición (CIBEROBN), Instituto de Salud Carlos III, Málaga, Spain; 3Department of Nutrition and Endocrinology, Instituto de Investigaciones Biomédicas de Málaga (IBIMA), University Hospital Virgen de la Victoria, Málaga, Spain; 4Department of Cardiovascular Surgery, University Hospital Virgen de la Victoria, Málaga, Spain Purpose: To evaluate if the preoperative administration of levosimendan in patients with right ventricular (RV) dysfunction, pulmonary hypertension, and high perioperative risk would improve cardiac function and would also have a protective effect on renal and neurological functions, assessed using two biomarkers neutrophil gelatinase-associated lipocalin (N-GAL) and neuronal enolase. Methods: This is an observational study. Twenty-seven high-risk cardiac patients with RV dysfunction and pulmonary hypertension, scheduled for cardiac valve surgery, were prospectively followed after preoperative administration of levosimendan. Levosimendan was administered preoperatively on the day before surgery. All patients were considered high risk of cardiac and perioperative renal complications. Cardiac function was assessed by echocardiography, renal function by urinary N-GAL levels, and the acute kidney injury scale. Neuronal damage was assessed by neuron-specific enolase levels. Results: After surgery, no significant variations were found in mean and SE levels of N-GAL (14.31 [28.34] ng/mL vs 13.41 [38.24] ng/mL), neuron-specific enolase (5.40 [0.41] ng/mL vs 4.32 [0.61] ng/mL), or mean ± SD creatinine (1.06±0.24 mg/dL vs 1.25±0.37 mg/dL at 48 hours). RV dilatation decreased from 4.23±0.7 mm to 3.45±0.6 mm and pulmonary artery pressure from 58±18 mmHg to 42±19 mmHg at 48 hours. Conclusion: Preoperative administration of levosimendan has shown a protective role against cardiac, renal, and neurological damage in patients with a high risk of multiple organ dysfunctions undergoing cardiac surgery. Keywords: levosimendan, preoperative, kidney, brain, acute renal failure